Religious Tolerance in the Quran and Sunnah and the Importance of Its Application in Indonesiaالتسامح الديني في ضوء القرآن والسنة وأهمية تطبيقه في اندونيسيا - Umma Farida (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2019)
This article aims at explaining the concept of religious tolerance according to the Quran and Sunnah, considering that many Indonesian people do not understand these Islamic teachings. They live in different islands with the diversity of religions, races, and cultures that can be a valuable asset for the building of multicultural Indonesia, while also potentially causing the social conflicts that divide their unity. Islam, as the religion of mercy for the worlds, provided the foundations for the importance of recognizing the religious, ethnic and cultural diversity. The Qur'an and Sunnah called to the religious tolerance, compassion, and harmony between Muslims and others, and forbade them from insulting the polytheists because the method of Prophetic call is far from coercion and fanaticism. The Prophet PBUH was the most salient and glorified of the conduct of peace and tolerance. He is the leader of the first nonviolent peaceful movement in the history of the world and the champion of peace. If the religious tolerance is being built as Islam has decided, then noble universal values such as justice, humanity, peace, and human well-being can be enforced, along with harmony and peace among the religions in Indonesia. تهدف هذه المقالة تبيين مفهوم التسامح الديني وشرحه وفقا للقرآن الكريم والسنة النبوية الشريفة، بالنظر إلى الواقع الذي يدل على أن الكثير من المسلمين لايفهمون هذه التعاليم الإسلامية بما فيهم الشعب الإندونيسي. إنهم يعيشون في الجزر المختلفة بتنوع الأديان والأعراق والثقافات. ويمكن أن يكون هذا التنوع رصيدا قيما لبناء اندونيسيا متعددة الثقافات، وفي نفس الوقت يحتمل أيضا أن يسبب الصراعات الاجتماعية التي تفرق وحدتهم.لقد وفر الإسلام كدين الرحمة للعالمين الأسس لأهمية الاعتراف بالتعددية الدينية والعرقية والثقافية وتنوعها، وهي ظاهرة ضرورية اقتضتها الفطرة الإنسانية واستلزمتها التنشئة الاجتماعية. وقد دعت الآيات القرآنية والأحاديث النبوية خير دعوة علمية وعملية إلى التسامح الديني والتراحم والتآلف بين المسلمين وغيرهم، وحرمتهم عن سَبّ المشركين وشتم عقائدهم، وذلك لأن أسلوب الدعوة المحمدية بعيدة كل البعد عن الإكراه والتعصب. فالنبي صلى الله عليه وسلم كان أبرز تجلٍّ ومصداق لسلوك منهجية السلام والتسامح، وهو صلى الله عليه وسلم قائد الحركة السلمية اللاعنفية الأولى في تاريخ العالم، وحامل راية السلم والسلام. واذا تم بناء التسامح الديني كما قرره الإسلام، فمن المتوقع أن القيم العالمية النبيلة، مثل الحق والعدالة والإنسانية والسلام ورفاهية البشرية يمكن إنفاذها، بجانب تحقيق الوئام والسلام بين المتدينين في إندونيسيا.